Horizons and Conscience (EAAE Annual Conference Proceedings, 2019)
What world does a European student imagine as they look beyond the Academy towards their future professional life? What horizons can they see which we cannot? Does that picture engage their moral compass, tracking the pressing contemporary issues from Planetary Environmental Crisis to the fragility of the Global South? How do they, as members of an increasingly international community, navigate that moral complexity? When their own future is unclear, how can they design the human future? ‘Horizons’ could be the sixth thematic area in this conference. ‘Horizons’ is closely linked to ‘Conscience’; the former involving looking outwards and the latter involving looking inwards.
Keywords: collaboration; Global South; student; wellbeing; agency